Neuropsychiatric symptoms and functional decline in alzheimerʼs disease and lewy body dementia (2020)
Background/objectives: Functional status is one of the most important markers of well-being in older adults, but the drivers of functional decline in dementia are not well known. The aim of our work was to study the association of neuropsychiatric symptoms (NPSs) with functional decline over 5 years in newly diagnosed people with Alzheimer´s disease (AD) and Lewy body dementia (LBD). Design: Secondary analysis of the Dementia Study of Western Norway longitudinal cohort study. Setting: Multicenter study conducted in memory clinics in western Norway. Participants: We included a total of 196 patients newly diagnosed with AD (n = 111) and LBD (n = 85), followed up annually for 5 years. Main Outcomes and Measures: The outcome was the rapid disability rating scale (items 1-13). Linear mixed-effects models were used for analysis with the total score of the Norwegian Neuropsychiatric Inventory (NPI) as a predictor measured either at baseline or longitudinally, adjusted for potential confounders, including cognition. Effect modification was checked by introducing interactions with NPI score and stratifying by diagnosis. Results: The total NPI score longitudinal course was associated with functional decline in both AD and LBD. At baseline, the total NPI score predicted functional decline in AD. Conclusion: NPSs were associated with the rate of functional decline in people with AD and LBD, independent of cognitive impairment. These results highlight the relevance of early detection and intervention of NPSs, which may also reduce functional decline.